Body Image and the Aging Female - Eboni J. Baugh (EDIS)
FCS-2299, a 4-page illustrated fact sheet by Eboni J. Baugh, highlights research examining the body image concerns among aging and elderly women. Includes references. Published by the UF Department of Family Youth and Community Sciences, May 2009. Reprinted December 2019.